Characterization, antibacterial activity, and stability of supercritical fluid extracted lemongrass nanoemulsion on Bacillus cereus - Mohd Daud, Ili Syuhada; Mahmud Ab Rashid, Nor Khaizura; Palmer, Jon; Flint, Steve (Elsevier, 2025)
Natural food preservation is a sustainable approach to extend shelf life, combat foodborne pathogens and enhance food safety. Bacillus cereus, a resilient contaminant, poses challenges due to its spore-forming ability and association with foodborne illnesses. This study investigates the characterization, antimicrobial activity, and stability of lemongrass (Cymbopogon citratus) nanoemulsions, extracted using supercritical fluid extraction (SFE), and their efficacy against B. cereus isolates (ATCC 14579, P4, and M2). Lemongrass oil was extracted at 85, 100, 200, and 300 bar, with the highest yield (0.815 %) obtained at 300 bar. Nanoemulsions were formulated with lemongrass extract and commercial citral, characterized for droplet size, polydispersity index (PDI), conductivity, and zeta potential, and assessed for antimicrobial activity. Lemongrass nanoemulsions initially had droplet sizes of 86.32 ± 0.66 nm, but increased over six months due to coalescence, with PDI values rising from 0.50 ± 0.00 to 0.81 ± 0.27, indicating reduced stability. Although zeta potential declined from −44.01 ± 1.69 mV to −33.63 ± 1.45 mV, it remained within the stable range (>±30 mV), maintaining sufficient electrostatic repulsion to prevent rapid aggregation. At 2.0 % concentration, nanoemulsions effectively suppressed B. cereus isolates (<1.00 CFU/mL), though efficacy declined after four months with increasing droplet size. Lemongrass nanoemulsions exhibited comparable antibacterial activity and stability trends to citral, suggesting that whole lemongrass extract retains its bioactivity as effectively as its major compound. Improved stabilization strategies, such as polymer encapsulation, could enhance shelf life, expanding applications in food preservation.